Translation, cross-cultural adaptation and validity study of the "Play Nicely Program: The Healthy Discipline Handbook" for use in Brazil - Janaina Recanello Begui; Seth Scholer; Naiara Barros Polita; Maria Aparecida Baggio; Maria de Fátima Garcia Lopes Merino; Adriana Valongo Zani; Rosângela Aparecida Pimenta (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to describe the translation, cross-cultural adaptation and validity process of the "Play Nicely Program: The Healthy Discipline Handbook" for use in Brazil. Methods: a methodological study that followed the translation, back-translation, expert committee assessment, and pre-test steps. The Content Validity Index (CVI) was calculated for both the judge population and the pre-test population. Four translators, seven expert judges in the field of child health and thirty participants in the pre-test, including parents, teachers and healthcare professionals, participated in the study. Results: in experts' analysis (98.4%), a value of 100% of adequate assessments was obtained, and in the target population's analysis (89.5%), there were 100% of adequate assessments. In both analyses, suggested adaptations were made. Conclusios: cross-cultural adaptation and content validity into Brazilian Portuguese of the "Play Nicely Program: The Healthy Discipline Handbook" were considered adequate for application in the target population.